2018
DOI: 10.1177/0306624x18788510
|View full text |Cite
|
Sign up to set email alerts
|

PrisonersPerceptions About Postrelease Employment in Romania: Studying the Role of Human Capital and Labelling Factors in Explaining Optimism and Pessimism

Abstract: Prior evidence shows that prisoners' beliefs and perceptions have profound implications for their postprison success. This study shows which prisoners are more or less optimistic about their postrelease employment prospects and for what reason. Specifically, this study examines how pessimistic prisoners are about finding a job, finding an unskilled job, and finding a minimum-wage job. It also reveals whether variables drawn from labelling and human capital theories can explain between-individual differences in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…With regard to the 14 studies that examined consequences of stigma, nine found that stigma experiences were associated with poor well-being outcomes, including low self-esteem (Harris, 1976), low quality of life (McWilliams & Hunter, 2021), poor perceived health status (Redmond et al, 2020), mental health symptoms (K. E. Moore & Tangney, 2017), anticipated rejection (Dâmboeanu & Ramakers, 2019; K. E. Moore, Stuewig, et al, 2016), and anticipated secrecy/withdrawal coping (Ray & Dollar, 2014; Winnick & Bodkin, 2008, 2009).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to the 14 studies that examined consequences of stigma, nine found that stigma experiences were associated with poor well-being outcomes, including low self-esteem (Harris, 1976), low quality of life (McWilliams & Hunter, 2021), poor perceived health status (Redmond et al, 2020), mental health symptoms (K. E. Moore & Tangney, 2017), anticipated rejection (Dâmboeanu & Ramakers, 2019; K. E. Moore, Stuewig, et al, 2016), and anticipated secrecy/withdrawal coping (Ray & Dollar, 2014; Winnick & Bodkin, 2008, 2009).…”
Section: Resultsmentioning
confidence: 99%
“…CAUSES AND CONSEQUENCES OF CRIMINAL STIGMA poor well-being outcomes, including low self-esteem (Harris, 1976), low quality of life (McWilliams & Hunter, 2021), poor perceived health status (Redmond et al, 2020), mental health symptoms (K. E. Moore & Tangney, 2017), anticipated rejection (Dâmboeanu & Ramakers, 2019; K. E. , and anticipated secrecy/withdrawal coping (Ray & Dollar, 2014;Winnick & Bodkin, 2008, 2009. Stigma experiences were associated with greater delinquency and recidivism risk in five studies (Adams et al, 2003;Edwards, 1996;McGrath, 2014;K.…”
Section: Criminal Involvement Stigmamentioning
confidence: 99%
“…Since most public employees do not work together to undertake and manage departmental initiatives, a lack of coordination has led to irregular expenditure and overspending in many departments. For the transformation process to be successful, the activity of the key reform agencies and role-players must be well-coordinated (Danboeanu & Ramakers, 2018). This necessitates the creation of efficient coordination mechanisms as well as a collaborative work environment within the public sector.…”
Section: Lack Of Coordinationmentioning
confidence: 99%
“…Despite the benefits/impacts of education on incarcerated individuals and efforts of some international organizations to promote correctional education, there still exists a high rate of recidivism globally [18][19][20][21] which is attributed to low or no participation in education programmes while in incarceration [22,23]. Extant research has shown that not all correctional education results in effective rehabilitation [16,24].…”
Section: Introductionmentioning
confidence: 99%